Studi Putusan Pengadilan dalam Kasus Penganiayaan oleh Tahanan di Bawah Arahan Kepolisian: Sebuah Kajian Hukum - Basyaruloh Yahya, Adrik Zulham (IAIN Langsa, 2024)
The police, as an institution that should provide a sense of security to the community, are often involved in violations of the law themselves. One such case of legal violation involving members of the police occurred at the Banyumas City Police Station (Polresta Banyumas). Eleven members of Polresta Banyumas and ten detainees were involved in the criminal act of assault against a detainee in a theft case, which resulted in the detainee's death. Seven of the eleven members of Polresta Banyumas have been sanctioned for violating the code of ethics by failing to supervise the detainee, leading to the assault. Based on this, it is necessary to examine the legal consequences for detainees who commit acts of assault within the detention facility under orders from police officers. This research employs a normative juridical method, where the study is conducted by examining literature or secondary data using a case approach, a statute approach, and a conceptual approach. The results of this research explain that the defendants were merely following orders from the Banyumas City Police officers, who are the authorized authorities. Therefore, the detainees should be acquitted of all charges because they committed the assault not of their own volition but under the orders of the police officers as the authorized authorities.